Third-line tigecycline antibiotic for Acinetobacter Baumannii infection in feline pyothorax - Zulfa Ichsanniyati R. Ciwi Fadhlillah; Siti Zaenab; Deni Noviana; Sukmasari Arifah (ARSHI Veterinary Letters, 2020)
A one-year-old domestic shorthair male cat was presented to the clinic with severe dyspnoea. The cat has a history of recurrence bronchial disease with coughing as a major clinical sign. The cat never be hospitalized and clinical symptoms will disappear after antibiotic and glucocorticoid administration within a few days. On physical examination, the cat was dehydrated and apathetic. Dullness thoracic percussion was detected. Other organs out of thorax did not show abnormality. Thoracic radiography revealed pleural effusion. Purulent fluid was obtained by thoracocentesis and cytologic examination result was septic exudates. Hematological result was marked leukocytosis (59.69x10ˆ9 g/l). Enrofloxacin was given as empirical antibiotic until culture results released. On the 7th day of Enrofloxacin administration, there was only a slight decrease in leucocyte count. Bacterial culture results was Acinetobacter baumannii (A. baumanii) that are sensitive to Meropenem and Tigecycline from antibiotic resistance test. Previous antibiotic was stopped and replaced with intravenous Meropenem. Moderate decrease of leucocytes count (28.03x10ˆ9 g/l) obtained on day 18th of Meropenem treatment and patient shows good clinical sign progress. Meropenem resistancy were considered when leucocytes count increased on the 20th day as A. baumanii is extremely multi-resistant organism. Third-line Tigecycline was administered as the last choice use of antibiotic and stop after leucocyte returned to normal on the 7th day of the treatment. The cat is fully recovered from Acinetobacter Baumannii infection pyothorax treated using third-line Tigecycline antibiotics.